Impact of Changes in Macroeconomic Factors of Stock Price Performance: A Comparative Analysis of Pre Crisis And Crisis Periods - Ali, Norli (2001)
It is generally believed that changes in economy affect the stock market performance. It is also believed that changes in stock market in turn will influence the economy as stock market serves as a leading economic indicator. Many researchers such as Kwon and Bacon ( 1 997), Chen, Roll and Ross ( 1 986), ArlIT and Johnson ( 1 990) and many more have investigated this relationship. However, the findings have been somewhat inconclusive, and thus, there is a need for such study in Malaysia. The main objective of the study is to investigate whether the changes in Malaysian macroeconomic factors namely expected inflation, exchange rates, interest rates, industrial production, money supply and market return can explain its stock price variability both prior to the crisis and during the crisis periods. The study investigated which of these six macroeconomic factors significantly influence stock returns. The study also examined the nature of the relationship between the above macroeconomic variables and stock returns (negatively related, positively related, etc). To examine those relationships, monthly data were used. The analyses were divided into two sub-periods, which are January 1 987 to December 1 999 and January 1 987 to December 1 996. The study adopted the Arbitrage Pricing Theory and the Error Correction Model to observe the relationship between stock returns and macroeconomic variables (expected inflation, exchange rates, interest rates, industrial production, money supply and market return). The findings for sub-period January 1 987 to December 1 999 appear to suggest that Composite Index (a proxy for market return), money supply, interest rates and exchange rates were dominant factors in determining portfolio returns. Whereas market performance appeared to be the only common factor that significantly influenced the sectoral indices movement. Similar approaches were also employed for pre-crisis period, January 1 987 to December 1 996. The findings confirmed that interest rates, money supply and market return have significant effect on changes in portfolio returns. While market returns were found to be the only common factor that significantly influenced the sectoral indices. However, no significant relationship was observed between changes in exchange rates and stock returns. Other variables namely industrial production and expected inflation asserted weak influence on asset pricing during both sub-periods. Market performance, money supply and exchange rates apparently had a positive relationship with portfolio returns and sectoral indices return. In contrast, interest rates and portfolio returns as well as sectoral indices return were found to be negatively related. In conclusion, the study found that Malaysian stock market is highly influenced by the changes in Kuala Lumpur Composite Index (a proxy for market returns), money supply, interest rates and exchange rates.